Collective Responsibility for Global Crime: Limitations with the Liability Paradigm - FINDLAY, Mark (Institutional Knowledge at Singapore Management University, 2011)
The development of victim-centered and restorative international criminal trial justice is contingent on the introduction of innovative conceptualizations and unique methods to assess collective liability and responsibility. Presently, an inability to escape the confines of individual liability at the expense of embracing more collective concepts of responsibility obstructs the transformation expected of international criminal justice trial to advance the conflict resolution and peacemaking aims of the International Criminal Court among victim communities in practice. The ICC needs to embrace truth-telling as it does fact-finding in resolving collective perpetration and communitarian victimization. This requires a fundamental re-conceptualization of victimization as the appropriate international justice constituency. The transformed international criminal trial will consequentially engage with truth and responsibility, within a due process rights framework. Other models for ensuring the regulation of collective perpetration and satisfying victim community interests are critiqued. As the exemplar of international criminal trial justice the ICC (actually or symbolically) provides the institutional context for critically analyzing the future intersection between collective liability and communitarian responsibility.